CHANGES IN THE KALLIKREIN-KININ SYSTEM IN RATS OF DIFFERENT AGES UNDER CONDITIONS OF POLYTRAUMA - Pidruchna, S.R.; Stepanova, H.M.; Zakcharchuk, U.M.; Fedonyuk, L.Ya.; Nychyk, N.A.; Krytskyi, T.I. (World of Medicine and Biology, 2018)
Traumatism is one of the most difficult problems of our time, which has not only a medical but also a pronounced social character. This is due to the affection, mainly, people aged 20 to 49 years, that is, the most able-bodied part of the population. During the last few decades, injuries reliably hold the third largest cause of mortality worldwide and above all among young people.Important pathogenetic mechanisms of traumatic illness are changes in the prooxidant-antioxidant balance and the presence of violations of the kallikrein-kinin system (KKS). The kallikrein-kinin system (KKS) is a regulatory component aimed at adaption of organism to the conditions of the internal and external environment that are constantly changing. Currently, the KKS is ranked among the most intensively examined proteolytic systems of the body. The condition of the KKS indicators reflects the activity of the inflammatory reaction in the body, the condition of microcirculation, the morbidity. The KKS is one of the central systems that regulates homeostasis and implements adaptive-defense reaction. Representative of specific proteolysis is kallikrein (KK), which is formed from the precursor – prekallikrein (PKK). Proteolytic activity (PRA) in blood plasma is increased due to intracellular release of peptide-hydrolase from damaged tissues, due to the increase of catabolism processes. However, there are few publications that would distinguish the pathogenetic features of the impact of multiple injuries on the KKS condition, depending on age characteristics of the organism, not taking into account its influence on the early and late periods of this process.The goal of research is to establish the pathogenetic role of the KKS, taking into account the age peculiarities of the organism at the early and late stages after the simulation of polytrauma.Material and research methods. 126 non-linear white rats in the age of 3, 6 and 24 months were used in the experiment. In the first research group, severe injury was simulated in the aseptic conditions under a slight etheric anesthetic. The control group consisted of intact animals, which were kept under standard animal facility conditions. At 1, 3, 24 hours and 14 day after injury in the conditions of thiopental-sodium anesthesia blood was taken in rats for biochemical studies, following the principles of the European Convention for the Laboratory Animal Protection (Strasbourg, 1986). The serum of blood has been determined by the content of KKS, KK and PRA. The reliability of the differences in the comparison groups was determined based on the Student's test.Findings and discussion. After the simulation of polytrauma in all researched age groups of animals, the increase of specific proteolysis by index KK can indicate the activation of adaptive defense reserves. With age, a slight depletion of the defense mechanisms of the body is noted, as evidenced by the data we received about a less pronounced increase the KK level of old rats 24 -months old, compared with young and reproductive animals. In the reproductive and old rats 6 and 24 - months old after the simulation of polytrauma, enhancement of nonspecific proteolysis by PRA level there was no statistically significant difference between the researched age groups. This may indicate a stable activation of total proteolysis in these age groups. Conclusions. Activation of KKS indicators confirms the presence of inflammatory process in animals with polytrauma, with a tendency to its greater increase in young animals. Data were obtained in favor of stable activation of total proteolysis in reproductive and old animals.A promising direction for further research is the possibility of using an experimental model for screening the prognosis of the course of the traumatic process, taking into account the age and period of traumatic injury and changes in the kallikrein-kinin system.
Keywords: rats; age; polytrauma; kalikrein-kinin system